Modular Stimuli‐Responsive Valves for Pneumatic Soft Robots - Qiguang He; Rui Yin; Yucong Hua; Hang Shu; Xiaoheng Zhu; A. B. M. Tahidul Haque; Samuele Ferracin; Saheli Patel; Weijian Jiao; Jordan R. Raney (Advanced Intelligent Systems)
Pneumatic soft robots have several advantages, including facile fabrication, versatile deformation modes, and safe human–machine interaction. However, pneumatic soft robots typically rely on mechatronics to interact with their environment, which can limit their form factors and reliability. Researchers have considered how to achieve autonomous behaviors using the principles of mechanical computing and physical intelligence. Herein, modular responsive valves that can autonomously regulate airflow within pneumatic soft robots in response to various environmental stimuli, including light, water, and mechanical forces, are described. By combining multiple types of valves, autonomous logic gates and more advanced logical operations can be realized. Finally, it is demonstrated that responsive valves can be integrated with pneumatic soft robots, allowing autonomous morphing and navigation. This framework provides a strategy for creating autonomous pneumatic robots that can respond to multiple stimuli in their environment.